### Home > CCA2 > Chapter 5 > Lesson 5.1.3 > Problem 5-48

5-48.

*f*(*x*) = 5*x* − 3 and *g*(*x*) = (*x* − 1)^{2}, are shown at right. Homework Help ✎

Suppose

*f*(3), (not*x*= 3), is dropped into the*g*(*x*) machine. This is written as*g*(*f*(3)). What is this output?Using the same function machines, what is

*f*(*g*(3))? Be careful! The result is different from the last one because the order in which you use the machines has been switched! With*f*(*g*(3)), first you find*g*(3), then you substitute that answer into the machine named*f*(*x*) .

*f*(3) = 12

so *g*(*f*(3)) = *g*(12) = 121

*f*(*g*(3)) = 17